Is an additional cannulated screw necessary for unstable femoral neck fractures with comminuted posteromedial cortex by femoral neck system (FNS) fixation? a biomechanical and clinical study - Fan, Jixing; Hao, Youliang; Cao, Yuan; Cui, Zengzhen; Lv, Yang; Zhou, Fang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe purpose of this study was to explore the biomechanical property and clinical efficacy of femoral neck system (FNS) with an additional cannulated screws (CS) in the treatment of unstable femoral neck fracture (FNFs) with comminuted posteromedial cortex.MethodsFirstly, we developed a model of Pauwels type III FNF with comminuted posteromedial cortex for the finite element analysis (FEA). Two experimental models were set up: the FNS model and the FNS + CS model. The von Mises stress on the proximal femur, implant and the total displacement of the device components were evaluated for both FNS and FNS + CS models. Secondly, we retrospectively included the cases of vertical FNFs with comminuted posteromedial cortex by FNS or FNS + CS fixation in our hospital from January 2020 to December 2023. In this study, demographic information, femoral neck shortening, Harris score of hip joint function, and postoperative complications were collected and compared.ResultsThe FEA results showed similar peak von Mises stress of the implant in two models and the additional CS could share the stress concentration with the FNS in the FNS + CS model. In terms of proximal femur, the maximum von Mises stress of the FNS model increased by 15.43% when compared with the FNS + CS model, and the magnitude of these two models were 83.02 MPa and 71.92 MPa, respectively. Furthermore, the maximum displacement in the FNS + CS model was much smaller than that in the FNS model. Clinically, the femoral neck shortening distance was significantly longer in the FNS group (5.62 ± 3.32 mm) than that in the FNS + CS group (3.49 ± 2.01 mm) (p = 0.027). Furthermore, the incidence of moderate to severe shortening (≥5 mm) was significantly higher in the FNS group compared with the FNS + CS group (p = 0.039). Moreover, the patients in the FNS + CS group had a higher Harris score than patients in the FNS group (91.97 vs. 88.56, p = 0.003).ConclusionCompared to the FNS alone, the FEA results showed that the FNS + CS had better biomechanical properties and the clinical results showed that the FNS + CS had a shorter femoral neck shortening and higher Harris score in treating unstable FNFs with comminuted posteromedial cortex.